PERAN PERAWAT DALAM TATALAKSANA DIARE AKUT PADA ANAK DI RS DR. SOEDJONO MAGELANG - , SEPTI WARDANI, Prof. dr. S. Yati Soenarto, Sp.A(K)., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: In Indonesia, the main cause of the high incidence of diarrhea in children is not yet precisely because of the treatment of diarrhea in children, either at home or in care. Nurses as health workers can perform its role in the management of acute diarrhea in children. The problems that arise in Indonesia is no clarity about the role of nurses in the management of acute diarrhea in children. Purpose: the purpose of this study to explore whether and how the role of nurses in the management of acute diarrhea in children in hospital dr. Soedjono Magelang. Methods: The method used was a qualitative study with a case study approach. Research subjects who are exposed to the nurse in the delivery of nursing care in children with acute diarrhea of five respondents. Samples were selected using purposive sampling method with homogeneous sampling strategy. Data were collected through interviews, documents, and participant observation, and analysis, we choose the model of Miles and Huberman. Triangulation is done in the validity and the research conducted from April to June 2014. Results: The result showed four categories, namely the role of the nurse as the service provider, collaborator, educator and protector. As caregivers, nurses perform assessments, documentation and evaluation of nursing care. As a collaborator, a nurse to collaborate with physicians to provide intravenous fluids, ORS, zinc, antibiotics, antidiarrheal not given and given a prebiotic, then collaborative healthcare analyst with blood tests and stool. As educators, nurses educate the administration of zinc, eating and advice. Nurses also conduct the informed concent in the administration of antibiotics as a form of role as protector. Conclusion: The nurse has to perform its role in the management of acute diarrhea in children in four areas, but there are weaknesses in the implementation of the nurse's role. The disadvantage is not done assessment of disease history, documenting the nurse has not done in an integrated manner, and severe dehydration determination has not been done properly. Further still given intravenous fluids in all children with acute diarrhea on the instructions of the doctor, antibiotics and prebiotics are still given. In addition, the nurse has not given duration of administration and education about the benefits of zinc and not made in the provision of informed consent documentation. Keywords : the role of nurses , acute diarrhea , management of diarrhea